Optimal Design of Lifting Platform Balance Control Algorithm: Co-Simulation and Experiment - Xin, Wang; Miao, Xu; Weiwei, Li; Miedzinski, Bogdan; Shumao, Wang (Elektronika ir Elektrotechnika, 2017)
The paper deals with balance control problem of lifting platform, collecting detailed first-hand information on its operation in reality. Sums up main challenges to be faced under processing of balance control. Recommends creative and representative control algorithms, comprehensively analysed basing on target platform developed by authors with respective following verification by simulation and testing. Relevant study was performed under three following steps: mathematical modelling, control system design and system verification. Therefore, dynamic model and ADAMS model have been established first based on actual structure of lifting platform. Next, a suitable control algorithm was selected and parameters of target models were set up using ADAMS/MATLAB co-simulation. Finally, both simulation and test results have been verified and compared to show their coincidence. It was found that control algorithms recommended in this paper can effectively improve as stability, reliability as well as security of operation of the lifting platform and can solve as a result the balance control problem of lifting platform at some extent in practice. DOI: http://dx.doi.org/10.5755/j01.eie.23.5.19237